A case study on thermal performance assessment of a heat exchanger tube equipped with regularly-spaced twisted tapes as swirl generators - Eiamsa-Ard, P.; Piriyarungroj, N.; Thianpong, C.; Eiamsa-Ard, S. (My University, 2014)
Effects of the regularly-spaced twisted tape (RS-TT) on the heat transfer, friction factor and thermal performance factor behaviors in a heat exchanger are reported along with those of a full length twisted tape. The full length (or typical) twisted tapes with two different twist ratios (y=P/W = 6.0 and 8.0), and the regularly-spaced twisted tape (RS-TT) with two different twist ratios (y=6.0 and 8.0) and three free space ratios (s=S/P = 1.0, 2.0, and 3.0) were employed for comparative study. The article also presents the application of a mathematical model for numerical simulation of the swirling flow in a tube induced by regularly-spaced twisted tape (RS-TT) insertion. The numerical simulation was performed in order to gain an understanding of physical behavior of the fluid flow (decaying swirling flow field), fluid temperature and local Nusselt number characteristics of a tube fitted with RS-TT in the turbulent flow regime. The Navier-Stokes equation in common with the energy equation was solved using the SIMPLE technique with the RNG k-ε turbulence model. The experimental results show that heat transfer rate and friction increased with decreasing twist ratio and space ratio. At similar conditions, full length twisted tapes (s=0) offered higher heat transfer rate, friction factor and thermal performance factor than RS-TT ones (s = 1.0, 2.0 and 3.0) as they induced more consistent swirling flows and thus turbulence. This reveals that it is possible to gain promising tradeoff between enhanced heat transfer and increased friction by selecting the twisted tape with proper geometries.
Keywords: Heat transfer; Regularly-spaced twisted tape; Swirl flow; Twisted tape